A Fiqh Siyasah Analysis of the Implementation of Article 64 of Bandar Lampung’s Regional Regulation on Public Order - Jemmy Aldiyantoro; Fathul Mu’in; Abidin Latua (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
This study examines the implementation of Article 64 of Bandar Lampung Municipal Regulation Number 01 of 2018 concerning the prohibition of unauthorized alcohol sales and demonstrates the existence of a significant gap between normative design and empirical practice. Employing a qualitative socio-legal approach through a case study conducted in Sukarame District, the research reveals that policy ineffectiveness is not merely attributable to weaknesses in legal norms, but rather to the complex interaction among limited institutional capacity, inconsistent law enforcement, community economic vulnerability, and the weak internalization of legal norms within social life. These conditions indicate that illegal alcohol distribution practices function as adaptive responses to the disjunction between formal regulation and socio-economic realities.  The principal contribution of this study lies in the operationalization of siyāsah tanfīdziyyah as an analytical framework for evaluating public policy implementation. The findings demonstrate that the principles of legal implementation, justice, public welfare, and accountability have not been fully realized in practice. Accordingly, effective policy implementation requires a multidimensional approach encompassing the strengthening of institutional capacity, consistency in law enforcement, the integration of socio-economic policies, and the enhancement of public legal consciousness.